Tuning the size and shape of nano-boehmites by a free-additive hydrothermal method. Issue 10 (19th November 2014) - Pardo, Pablo; Montoya, Noemí; Alarcón, Javier
Abstract : Nano-boehmites with a range of controlled sizes and morphologies exhibiting high dispersability in water were synthesized through a free-additive hydrothermal methodology. Abstract : A synthetic procedure allowing the control of boehmite micro and nanoparticles is presented. The proposed hydrothermal synthetic procedure is based on the control of three reaction parameters, the pH and temperature of precipitation of xerogels and the water/xerogel ratio for the hydrothermal process, carried out at 200 °C for 48 h. Results obtained by measurements on transmission electron microscopy (TEM) images indicate that at pH 5 micro or nanorods of controlled length between ca. 300 and 50 nm were obtained depending on the temperature of precipitation of the xerogel (25 or 100 °C) and the water/xerogel ratio used (1/1, 6/1, 15/1). On the contrary, at pH 10, nanoplatelets with major basal dimensions ranging between 50 and 25 nm were prepared with the same values of the mentioned parameters. The implemented methodology for the particle-length determination based on the accumulation of measurements on TEM images was in good agreement with the results obtained from dynamic light scattering (DLS) measurements for properly dispersed boehmite nanoparticles, validating its application in the study of these materials. On the basis of X-ray diffraction (XRD) broadening analysis, high-resolution transmission electron microscopy (HRTEM) images and zeta potential ( ζ ) results, some details on the mechanism of formation of the final boehmites prepared by hydrothermal aging of precipitated xerogels have been proposed.